What are the elements of the tobacco endgame?. Issue 2 (16th February 2012) - Thomson, George; Edwards, Richard; Wilson, Nick; Blakely, Tony
Abstract : The available literature on tobacco endgames tends to be limited to discussing means, targets and difficulties. This article offers additional ideas on the key elements of endgame strategies and the circumstances in which these are likely to be adopted and implemented. We suggest such strategies will include explicit plans, will define the nature of `the end of tobacco use/sale' and have target dates within 20 years. The likely circumstances for endgame strategy development include low (probably under 15% adult smoking) prevalence and/or rapid prevalence reductions, wide support and strong political leadership. Even with some or all these circumstances, opposition from business, internal government forces and international factors may influence results.